Using MCA methodology in the mining industry to aid in achieving sustainable management: Case study in the Peruvian mining industry - Poterico Huamayalli, Julio Gregorio; Filomon, Laurente-Rosas (Edelweiss Applied Science and Technology, 2024)
Quantifying the positive and negative impacts on mining activity is precisely knowing how this activity has been operating. Indeed, in this work its central objective is to quantify the impacts evaluated from a holistic perspective. The positive and negative impacts generated by mining activity in part of the northern region of Peru have been collected, analyzed and evaluated. For the evaluation of externalities, the multiple criteria evaluation (MCA) methodology has been used as a basis, which has been improved by including adjustment factors or weights, both for the components and for the evaluation variables. The calculations of the adjustment factors have been carried out for both the assigned weights and the calculated weights. The impacts obtained through assumed adjustment factors represent 41.50% for positive impacts and 58.50% for negative impacts, while the impacts obtained through the calculated weights were 44.96% for the positive ones and 55.04% for the negative ones. Consequently, multi-criteria assessment of the impacts generated by mining activity using an enhanced multi-criteria assessment with calculated weights is more recommended. It concludes with suggestions for the Peruvian government, mining entrepreneurs and other interested actors to improve the credibility of mining and thus achieve a social license to operate.